The Acculturation Strategy Preference of Londo Kampung’s Family Depicted from Language Choice - Anjanillah, Farah (ICONELT, 2024)
The grand theme of transnational migration has been intriguing to be discussed in the sociolinguistics field, taking into account that a dispersion possibly creates a dilemma among diaspora to adjust their culture and language in the host land in order to coexist. Thus, the researcher of this study investigated the acculturation strategy preference of Londo kampung’s family as an Australian diaspora to stay in Surabaya, Indonesia, depicted from their language choices. Using a qualitative case study design, the data of this study were gathered from a YouTube channel named Londokampung. The results exhibit that the family members of Londo kampung favor to implement an integration strategy indicated through the use of English in the family domain to maintain their identities. Moreover, this strategy is also signaled through the use of the host society’s languages in the friendship domain. As a way to blend with the host society, Londo kampung’s parents are able to speak Indonesian language, meanwhile Londo kampung could speak both Javanese and Indonesian language. Conversing about the factors of language choice, the researcher concludes that the language choice of Londo kampung’s family members are controlled by several factors comprising the participant, group membership, social distance, status relationship, setting, formality degree, the linguistic repertoire similarity, and third person presence or non-participating audience. To wrap it up, the integration strategy and opted by Londo kampung’s family leads to the attainment of bilingualism and multilingualism benefits such as positive intercultural relation as well as career success in the host country.